Consequences of a Diagnostic Label: A Systematic Scoping Review and Thematic Framework - Sims, Rebecca; Michaleff, Zoe A.; Glasziou, Paul; Thomas, Rae (Frontiers in Public Health, 2021)
Objectives. To develop a thematic framework for the range of consequences arising from a diagnostic label from an individual, family/caregiver, healthcare professional, and community perspective. Design. Systematic scoping review of qualitative studies. Search Strategy. We searched PubMed, Embase, PsycINFO, Cochrane, and CINAHL for primary studies and syntheses of primary studies that explore the consequences of labelling non-cancer diagnoses. Reference lists of included studies were screened, and forward citation searches undertaken. Study selection. We included peer reviewed publications describing the perceived consequences for individuals labelled with a non-cancer diagnostic label from four perspectives: that of the individual, their family/caregiver, healthcare professional and/or community members. We excluded studies using hypothetical scenarios. Data extraction and synthesis. Data extraction used a three-staged process: one third was used to develop a preliminary framework, the next third for framework validation, and the final third coded if thematic saturation was not achieved. Author themes and supporting quotes were extracted, and analysed from the perspective of individual, family/caregiver, healthcare professional, or community member. Results. After deduplication, searches identified 7379 unique articles. Following screening, 146 articles, consisting of 128 primary studies and 18 reviews, were included. The developed framework consisted of five overarching themes relevant to the four perspectives: psychosocial impact (e.g., positive/negative psychological impact, social- and self-identity, stigma), support (e.g., increased, decreased, relationship changes, professional interactions), future planning (e.g., action and uncertainty), behaviour (e.g., beneficial or detrimental modifications), and treatment expectations (e.g., positive/negative experiences). Perspectives of individuals were most frequently reported. Conclusions. This review developed and validated a framework of five domains of consequences following diagnostic labelling. Further research is required to test the external validity and acceptability of the framework for individuals and their family/caregiver, healthcare professionals and community.